METODOLOGI PEMBELAJARAN MAHAROTUL KALAM - Koiruman, Joko Andi (TAZKIRAH, 2025)
The teaching method is an important component in the success of Arabic learning activities inside and outside the classroom. That is without a suitable method and manner then learning the Arabic language will not run properly and smoothly, in addition students will feel tired and bored so as no passion to learn Arabic language and will treat Arabic as a difficult language to learn. Some researches suggest that methodology is the most dominant factor in the success of Arabic learning, because the proper method will encourage and motivate students to keep and continue learning and developing their Arabic language skills.